Influence of coadsorbed H in CO dissociation and CH n formation on Fe (100): A DFT study - Amaya Roncancio, Sebastian (2015)
Density Functional Theory (DFT) was employed to study the influence of coadsorbed hydrogen in CO dissociation and C hydrogenation on Fe(100). The formation of species CHn (n = 1, 2, 3) from the reaction CHn−1 + H as well as CO dissociation was analyzed in terms of hydrogen coverage. The active sites for the adsorption and reaction of each intermediate product on the catalytic surface and the reaction pathways of the products were determined. Mulliken population analysis was carried out to evaluate the charge transfer in the CHn/Fe system. It was observed that carbon transfers charge in all cases, while the catalyst transfers charge principally in the adsorption of CH2 and CH3. To determine the effect of hydrogen on CO dissociation and CHn formation, coverages of 0, 0.25, 0.50 and 0.75 monolayers of hydrogen were employed. The CO adsorption energy shows slight variations in the presence of hydrogen, while in CO dissociation the variations of the barriers were negligible. In CHn adsorption, slight changes in the energies were observed. The reaction of C hydrogenation exhibited sensitivity to the presence of hydrogen, showing that CH and CH2 formation were endothermic processes, while CH3 formation showed an exothermic or endothermic behavior, depending on the final adsorption configuration.